Collected tales, sketches, speeches and essays 1891 - 1910 - Twain, Mark (The Library of America, 1992)
Mark Twain is well known for his Mississippi Novels and Historical Romances but it's on his Tales and Sketches where you can find the commical genious in him. It's in my opinion that it's an age span wich makes you like the most Tom Sawyer (8-12), The Prince and the Pauper (13-16) or The Diary of Adam and Eve (18-) and yet, in his complete tales you may find contents of interest for all kinds of readers